Intergroup Randomized Phase III Study of Postoperative Oxaliplatin, 5‐Fluorouracil, and Leucovorin Versus Oxaliplatin, 5‐Fluorouracil, Leucovorin, and Bevacizumab for Patients with Stage II or III Rectal Cancer Receiving Preoperative Chemoradiation: A Trial of the ECOG‐ACRIN Research Group (E5204). (18th December 2019) - Chakravarthy, A. Bapsi; Zhao, Fengmin; Meropol, Neal J.; Flynn, Patrick J.; Wagner, Lynne I.; Sloan, Jeffrey; Diasio, Robert B.; Mitchell, Edith P.; Catalano, Paul; Giantonio, Bruce J.; Catalano, Robert B.; Haller, Daniel G.; et al.
Abstract: Background: The addition of bevacizumab to chemotherapy improved outcomes for patients with metastatic colon cancer. E5204 was designed to test whether the addition of bevacizumab to mFOLFOX6, following neoadjuvant chemoradiation and definitive surgery, could improve overall survival (OS) in patients with stage II/III adenocarcinoma of the rectum. Subjects, Materials, and Methods: Patients with stage II/III rectal cancer who had completed neoadjuvant 5‐fluorouracil‐based chemoradiation and had undergone complete resection were enrolled. Patients were randomized to mFOLFOX6 (Arm A) or mFOLFOX6 with bevacizumab (Arm B) administered every 2 weeks for 12 cycles. Results: E5204 registered only 355 patients (17% of planned accrual goal) as it was terminated prematurely owing to poor accrual. At a median follow‐up of 72 months, there was no difference in 5‐year overall survival (88.3% vs. 83.7%) or 5‐year disease‐free survival (71.2% vs. 76.5%) between the two arms. The rate of treatment‐related grade ≥ 3 adverse events (AEs) was 68.8% on Arm A and 70.7% on Arm B. Arm B had a higher proportion of patients who discontinued therapy early as a result of AEs and patient withdrawal than did Arm A (32.4% vs. 21.5%, p = .029).The most common grade 3–4 treatment‐related AEs were neutropenia, leukopenia, neuropathy, diarrhea (without prior colostomy), and fatigue. Conclusion: At 17% of its planned accrual, E5204 did not meet its primary endpoint. The addition of bevacizumab to FOLFOX6 in the adjuvant setting did not significantly improve OS in patients with stage II/III rectal cancer. Implications for Practice: At 17% of its planned accrual, E5204 was terminated early owing to poor accrual. At a median follow‐up of 72 months, there was no significant difference in 5‐year overall survival (88.3% vs. 83.7%) or in 5‐year disease‐free survival (71.2% vs. 76.5%) between the two arms. Despite significant advances in the treatment of rectal cancer, especially in improving local control rates, the risk of distant metastases and the need to further improve quality of life remain a challenge. Strategies combining novel agents with chemoradiation to improve both distant and local control are needed. Abstract : Despite advances in the treatment of rectal cancer, the risk of distant metastases and poor quality of life remain a challenge. Trial E5204 was designed to test whether the addition of bevacizumab to mFOLFOX6, following neoadjuvant chemoradiation and definitive surgery, could improve overall survival in patients with stage II/III adenocarcinoma of the rectum.